2016
DOI: 10.4088/jcp.15cr10451
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavioral Therapy for Olfactory Reference Syndrome

Abstract: was carried out with 8 fellow group members who were all suffering from body dysmorphic disorder (BDD). Treatment consisted of twice-weekly sessions with a total duration of 16 weeks. CBT was based on a previously published manual, 13 which was adapted to facilitate group-based treatment. The first session entailed psychoeducation and establishment of treatment goals. In the second session, an exposure hierarchy was composed. During and between sessions, gradual and repetitive in vivo exposure with task concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…CBT has proven to be helpful not only for anxiety, depression, OCD and BDD, but it has shown to substantially benefit ORS patients with full remission after only 2 months. 14 Similarly, in our case patient showed exceptional improvement and full remission after 3 months of offering treatment.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…CBT has proven to be helpful not only for anxiety, depression, OCD and BDD, but it has shown to substantially benefit ORS patients with full remission after only 2 months. 14 Similarly, in our case patient showed exceptional improvement and full remission after 3 months of offering treatment.…”
Section: Discussionsupporting
confidence: 72%
“…A meticulous search of the literature, however, proves CBT to be effective both alone and in combination with pharmacotherapy. 12,[14][15][16]18,19 In our case, the patient experienced foul body odor, anxiety, and paranoia after a stressful triggering event. We believe that our patient might have lost insight early on in her illness.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The research evidence on mechanisms and treatment of ORD is scant. Interventions using pharmacotherapy have been reported using SSRIs or SSRI with antipsychotic augmentation (Dominguez & Puig, 1997;Michael, Boulton, & Andrews, 2014;Stein, Le Roux, Bouwer, & Van Heerden, 1998) but only three case reports using psychological therapy have been reported, two with successful use of an exposure and response prevention rationale (Martin-Pichora & Antony, 2011, Zantvoord, Vulink, & Denys, 2016) and a case series utilising EMDR (McGoldrick, Begum, & Brown, 2008). Disorder specific treatment guidelines…”
Section: Theoretical and Research Basis For The Treatmentmentioning
confidence: 99%
“…Another potential for ORD treatment is cognitive behavioral therapy (CBT). Some previous case reports have suggested that utilizing CBT adjusted for obsessive–compulsive disorder (OCD) models could potentially reduce ORD symptoms 4,9,10 . The CBT model has been successful in treating female patients in the UK, the USA, and Australia 4,10,11 .…”
Section: Introductionmentioning
confidence: 99%